Revisiting the Relationship Between Deception and Design: A Replication and Extension of Hancock et al. (2004). (8th November 2021) - Markowitz, David M
Abstract: Evidence published nearly 20 years ago suggested people tell more lies per social interaction via synchronous, distributed, and recordless media (the phone) versus relatively richer (face-to-face communication) and leaner media (email, instant messaging). With nontrivial changes to the size and variety of our media landscape, it is worth re-examining the relationship between deception and technology. Over 7 days, 250 participants reported their social interactions and lies across face-to-face communication, social media, texting, the phone, video chat, and email. Replicating Hancock, Thom-Santelli, and Ritchie (2004), people told the most lies per social interaction over synchronous, distributed, and recordless media (the phone, video chat), though the effects were small and between-person effects explained more variance than between-media effects. Lying rates were also associated with aversive personality traits, plus antisocial, and relational deception motives. Together, while media options have evolved, technological design features often remain stable and indicate deception rates. Theoretical contributions are discussed.